TO THE QUESTION ABOUT FEATURES OF ISOLATED DIVISIONS OF A LEGAL PERSON IN CIVIL LAW THEORY - K. V. Chernova (Гуманитарные и юридические исследования)
The article is devoted to the analysis of qualifying features of isolated divisions of legal persons. The author examines classical civilis, organizational and legal characteristics of the given isolated divisions, as well as controversial features that can be found in various branches of modern legislation.